Improving Pro-environmental Behavior: Voluntary and Social-Pressure Pathways in Indonesia - Kuswati, Rini; Waskito, Jati; Ajeng Pramesti , Diesyana; Shoxrux Ulugbekovich, Ibragimov (JBTI : Jurnal Bisnis : Teori dan Implementasi, 2026)
The study focuses on developing a model of pro-environmental behaviour. Another pressing matter is determining whether pro-environmental behaviour is voluntary or non-voluntary. This study examines the impact of social pressure and pro-environmental self-identity on such behaviour, with pro-environmental views acting as a mediator variable. The study employed a positivist paradigm and used quantitative techniques in the form of an online survey. The research design involved a diverse group of participants, including adolescents and adults from Indonesia. A total of 653 Indonesian respondents were selected from various islands in Indonesia. Using Smart PLS to analyse the data, this study demonstrates that social pressure and pro-environmental self-identity substantially and favourably impact pro-environmental attitudes, based on empirical evidence. Recent research shows that pro-environmental activity in Indonesian society tends to be voluntary rather than compulsory.  This study provides empirical evidence that the combination of social influence and self-identity theories can effectively explain voluntary pro-environmental behaviour.